ANALYSIS OF THE INFLUENCE OF ORGANIZATIONAL CULTURE AND EMPLOYEE MOTIVATION ON HR PERFORMANCE AT THE REGIONAL REVENUE AGENCY PESAWARAN REGENCY PROVINCE LAMPUNG - Khaidarmansyah Khaidarmansyah; Apriyadi Apriyadi; Supriyadi Supriyadi (Jurnal Ekonomi, 2023)
Human resources are the most important asset for an organization that is an active planner and actor of various activities within the organization. Human resources have thoughts, feelings, desires, status and educational background whose mindset can be brought into an organizational environment. The performance achieved by an organization is basically the achievement of the members of the organization itself, from the top to the bottom level. The concept of local government performance itself emerged when government institutions began to try to introduce new concepts in the management of public affairs into good governance. One of the problems that affects the performance of ASN employees at the Pesawaran Regency Regional Revenue Agency, Lampung Province is work culture, in which case the problem solving carried out by the leadership still predominantly comes from the leadership without listening to and considering the opinions of subordinates. As a result, most respondents felt underappreciated in solving problems that occurred, which resulted in a decrease in their performance. This research can contribute ideas to the leadership of the Regional Revenue Board of Pesawaran Regency, Lampung Province so that they can find out how Organizational Culture and employee motivation can affect HR performance, as well as other problems that arise in connection with HR performance at the Regional Revenue Board of Pesawaran Regency, Lampung Province. most respondents felt underappreciated in solving problems that occurred resulting in a decrease in their performance. This research can contribute ideas to the leadership of the Regional Revenue Board of Pesawaran Regency, Lampung Province so that they can find out how Organizational Culture and employee motivation can affect HR performance, as well as other problems that arise in connection with HR performance at the Regional Revenue Board of Pesawaran Regency, Lampung Province. most respondents felt underappreciated in solving problems that occurred resulting in a decrease in their performance. This research can contribute ideas to the leadership of the Regional Revenue Board of Pesawaran Regency, Lampung Province so that they can find out how Organizational Culture and employee motivation can affect HR performance, as well as other problems that arise in connection with HR performance at the Regional Revenue Board of Pesawaran Regency, Lampung Province.